L’histoire des idées dans la revue Recherches germaniques - Sonia Goldblum (Recherches Germaniques)
The aim of this article is to give an account of the place of the history of ideas as a research discipline in German studies within the journal Recherches germaniques. This particular status is placed in the context of the evolution of the history of ideas in France over the last fifty years. In order to do so, we rely on Gérard Raulet’s contribution entitled “Histoire des idées: une certaine idée de l’histoire”.